Is the Business in Saudi Market Sustainable? Case Study of Almarai - Mohamad, Khaliq Ahmad; Asfour, Ayman Mahmoud (IIUM Journal of Case Studies in Management, 2020)
Almarai is an international business originating from Saudi Arabia. The company has a reputable position in the MENA region. For many decades especially inside KSA (Kingdom of Saudi Arabia) in GCC including other Gulf countries and North Africa, Almarai enjoys brand leadership. The company ownership is diversified that consists of reputable owners including from the royal family, who concern tremendously to upgrade the economy of the Kingdom and raise social welfare as well. Guided by the kingdom’s vision-2030 there are stable companies including Almarai that have a continuous growth potentials as evident from its annual financial statements until a turning point, where profitability ratio has dipped and sustainability of its business is a question mark due to the Covid-19. The company has operated in range of business segments such as dairy, juices, cheese and agribusiness and its brand are known in supermarket shelves. Workers of the organization have diversity of nationalities and religions; Almarai requires a professional dealing with employees regarding the Islamic and fair business concepts which distributes the responsibilities and duties fairly without any kind of discrimination. The challenges ahead of the company are dual viz. to maintain reasonable return on investment for shareholders and employees retention in midst of devastating effect of post Covid-19 crisis and forthcoming economic downturn due to the unexpected pandemic for the year 2020 in short term and its’ pursuit of national agenda of achieving the kingdom vision 2030 in the long term.